2016
DOI: 10.12659/msm.902163
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy with Amplatz and Alken Dilators: An Eight-Year Single Tertiary Care Centre Experience

Abstract: BackgroundPercutaneous nephrolithotomy (PNL) is the standard procedure for patients with renal stones over 2 cm in diameter. We analyzed complications after this procedure focusing on two different methods of tract dilation.Material/MethodsBetween August 2008 and April 2016 222 percutaneous nephrolithotomies were performed in a total of 208 patients. The Group I (n=123) comprised patients where Alken dilatators were used, while Group II (n=99) comprised patients where Amplatz dilators were used. Efficacy was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Considering complication rates, RIRS may have a lower risk of severe complications compared to PCNL because the instruments used are of lower caliber and flexible, and operation is performed through direct vision. Bryniarski et al [18] have assessed outcomes after RIRS and PCNL. They have found that transfusion required in 13 of the PCNL patient group and no transfusion in the RIRS patients group [18] .…”
Section: Discussionmentioning
confidence: 99%
“…57 However, Alken dilators were shown to have higher infective complications due to the fact that an access sheath was not used during the study, and Amplatz dilators were associated with higher pleural injuries, as they were used more for intercostal puncture. 57 Both had similar stone-free rates and complication rates, with Alken dilators being more cost-effective. 58 Balloon dilatation has the advantage of less radiation exposure, but has a lower success rate, especially in patients with calyceal stones or staghorn stones 59 and previous renal surgery.…”
Section: Dilatation Of Tractmentioning
confidence: 95%
“…Both are equally safe and do not differ in terms of hemoglobin drop and blood transfusion . However, Alken dilators were shown to have higher infective complications due to the fact that an access sheath was not used during the study, and Amplatz dilators were associated with higher pleural injuries, as they were used more for intercostal puncture . Both had similar stone‐free rates and complication rates, with Alken dilators being more cost‐effective …”
Section: Pcnlmentioning
confidence: 96%
See 1 more Smart Citation